Cr-Al coatings on low carbon steel prepared by a mechanical alloying technique. (August 2016) - Hia, A I J; Sudiro, T; Aryanto, D; Sebayang, K
Abstract: Four different compositions of Cr and Al coatings as Cr10 o, Cr87 .5 Al12 .5, Cr5 oAl5 o, and Al100 have been prepared on the surface of low carbon steel by a mechanical alloying technique. The composition of each powder was milled for 2 hour in a stainless steel crucible with a ball to powder ratio of 10:1. Hereafter, the Cr-Al powder and substrate were mechanical alloyed in air for 1 hour. Heat treatment of coated sample were carried out at 800°C in a vacuum furnace. In order to characterize the phase composition and microstructure of the coating before and after heat treatment, XRD and SEM-EDX were used. The results show that Cr, Cr-Al or Al coatings were formed on the surface of low carbon steel. After heat treatment, new phases and interdiffusion zone were formed in the coating and at the coating/steel interface, depending on the coating composition.